Third-Year English Students’ Learning Experience with Google Translate: A Qualitative Exploration - Syukri, Restu Fitrahadi; Mahdum; Syarfi, Muhammad (PROJECT (Professional Journal of English Education), 2025)
This research explores the learning experiences of third-year English Study Program students in using Google Translate (GT) to support their academic language development, focusing on its practical use, impact on vocabulary and grammar, and related cognitive-emotional aspects. A qualitative approach was employed, using semi-structured interviews with ten participants. Thematic analysis revealed three key dimensions: engagement with the tool, academic development, and cognitive-emotional response. Participants reported that GT was highly practical, accessible, and useful for fostering independent learning. It contributed significantly to vocabulary learning and writing tasks, although grammar support was viewed with some caution. Students also showed awareness of GT’s limitations and reflected critically on their dependence on the tool. The findings suggest that GT, when used wisely, enhances language learning and supports academic success. The research concludes that GT is a helpful supplementary tool, provided students maintain critical engagement and avoid overreliance. Future research may explore the long-term effects of GT use on language proficiency and student autonomy.